Barriers to immigrant assimilation evidence on grading bias in Ecuadorian high schools - Marcos A. Rangel; Luana Marotta; Cynthia Van der Werf; Suzanne Duryea; Marcelo Drouet; Lucina Rodríguez Guillén (Inter-American Development Bank (IDB), 2024)
We investigate the assimilation of immigrant youth in Ecuador. Focusing on formal schooling and employing administrative data from high schools, we document subtle ways by which assessment biases against students with an immigrant background play a significant role in this assimilation process. We find that, after holding constant performance on blindly scored proficiency tests, teacher-assigned grades in Mathematics and Spanish are consistently lower for students from immigrant families. We show that these results are robust with respect to the omission of socio-emotional and behavioral traits that are likely valued by teachers. These differentials are larger for male students and those attending urban schools. While these grading differentials have direct impact over high school graduation rates, they may also discourage future human capital investments, potentially leading to lower college attendance, distorted choice of major, and suboptimal labor market outcomes, which are all well know elements for the economic assimilation of immigrants.
Keywords: I24; J15; 330; Immigration assimilation; human capital; teacher discrimination; grading bias